Colorant from selected rocks/soils / Wan Yunus Wan Ahmad ...[et al.] - Wan Ahmad, Wan Yunus; Abdul Hamid, Hushinaidi; Abdul Kadi, Muhammad Ismail; Abdul Kadir, Anis Jauharah; Imran, Mohamad Khalil; Salleh, Jamil; Mohd Yusoh, Mohd Kahiri (2006)
Selected rocks/soils were used as dyes to colour textile silk fabric. The rocks have to be grinded before being used as dyes or pigments. The dyeing techniques applied for the ground colour were exhaustion, brushing or painting method Wax and non-wax batik resist agents were used to draw the outlines of batik designs by canting The wax is also used to design batik by block printing The rocks/soils used were lateritic rocks with different amount of iron oxide contents and shale with aluminium and clay contents. The wash fastness and rubbing fastness properties of rocks/soils dyea and printed fabrics were within the range of fastness of natural dyes from other sources such as plants or animals. The application of rocks/soils dyes could implement the 'waste-to-wealth' principle by converting natural 'waste' to products as the rocks are easy to source, cheap and at the same time less toxic. The rocks/soils can also be used as pigmenf printing as well as tie and dye technique to form designs.